(untitled) - Kroupová, Ludmila (Aura musica, 2020)
The Children's Choir Jitro from Hradec Kralove has had forty-five years of successful operation in the field of choral singing. A brief treatise presents an overview of its concert activities, competition achievements and discography. The conclusion summarizes the choir principles and values that were established in its beginnings and according to which the choir works to these days.
Keywords: the Children's Choir Jitro from Hradec Králové; choral singing; overview of concert activities; discography; values of the choir